A Systematic Review: Aggregation Methods for Production Processes in Supply Chain Management - Cahya Pratama, Yudha Herlambang; Naristi, Keysa; Arifianti, Clariza (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
In the modern era, technology has significantly changed the way businesses operate, leading to the need for faster and more efficient processes, new technologies like robotics, machine learning, and artificial intelligence. This has enabled organizations to increase operational efficiency, increase customer experience, and remain competitive in the rapidly changing business environment. One strategy for implementing technology is through ideal generation planning, which involves planning the entire production process and operational planning. This approach helps companies optimize resources, reduce costs, and increase efficiency. In business management, aggregate planning is crucial for integrating various business functions, such as sales, production, and financial management, to achieve a company's full potential. However, implementation can be challenging due to various challenges, such as high production volumes and low volume. This study aims to explore the implementation of aggregate planning in business management, focusing on the impact of technology on efficiency and effectiveness of production planning. Based on the results of the analysis in the journal, it was found that production planning is important at the MSME business unit level. Chase Strategy is the right choice for production planning at the MSME business unit level. Information technology integration has proven critical to improving aggregate planning efficiency, although interdepartmental coordination challenges are a major obstacle. Therefore, it is necessary to implement centralized information technology that is able to unite the needs of each department to achieve overall business process efficiency and effectiveness.